Strategi Pengelolaan Sumber Daya Alam dalam Administrasi Pembangunan yang Berkelanjutan - Wahyudi Mokobombang (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze natural resource management strategies within the framework of sustainable development administration in Indonesia. Using a qualitative approach and policy analysis methods, the research evaluates existing regulations, institutional capacities, and the effectiveness of policy implementation in ensuring resource sustainability. The study examines a range of policy instruments, from sectoral regulations and decentralization mechanisms to community-based programs. Findings reveal that regulatory fragmentation, weak inter-agency coordination, limited local government capacity, and suboptimal governance practices constitute the primary challenges to sustainable natural resource management. The research affirms that an integrated and collaborative approach encompassing ecological, economic, and socio-cultural dimensions is a prerequisite for achieving sustainable development. Policy recommendations include regulatory reform, institutional strengthening, indigenous community empowerment, development of integrated monitoring systems, and mainstreaming sustainability principles throughout the national and regional development planning cycles.